An efficient image encryption scheme using gray code based permutation approach. (April 2015) - Chen, Jun-xin; Zhu, Zhi-liang; Fu, Chong; Yu, Hai; Zhang, Li-bo
Abstract: In recent years, the operation efficiency of chaos-based image cryptosystems has drawn much more concerns. However, the workload arised from floating point arithmetic in chaotic map iteration prevents the efficiency promotion of these cryptosystems. In this paper, we present a novel image encryption scheme using Gray code based permutation approach. The new permutation strategy takes full advantage of ( n, p, k )-Gray-code achievements, and is performed with high efficiency. A plain pixel-related image diffusion scheme is introduced to compose a complete cryptosystem. Simulations and extensive security analyses have been carried out and the results demonstrate the high security and operation efficiency of the proposed scheme. Highlights: We propose an efficient image cryptosystem with Gray-code based permutation approach. The new permutation approach is high efficiently implemented. A plain pixel-related image diffusion strategy is employed. The high security and efficiency of the proposed scheme is well demonstrated.